Oscar, Derrida’s Cat, and Other Knowing Animals - Wendy Harding; Jacky Martin (Transatlantica)
Man is a knowing animal. Knowledge is his distinctive mark. Yet in confrontations with animals, particularly in circumstances involving death, human knowledge suddenly appears limited. Other forms of knowledge have to be taken into account. The case of Oscar, the cat who predicts patients’ death in a Rhode Island hospital, indicates that animals know things that are concealed from us. Our knowledge is limited, a premise that Derrida analyses in The Animal that Therefore I Am, where he admits that the philosophical literature about animals does not satisfactorily justify his human difference. Barry Lopez shows that our knowledge is not only insufficient when it comes to accounting for the agony of a school of beached whales, but that it is a poor substitute for our perplexity in the face of death. Heidegger’s analysis in Being and Time offers an affirmative conception of the confrontation with death. Death ceases to be the destabilizing nothingness that threatens our existence and instead provokes knowledge. The study of two correlated texts, by Dickey and Dillard helps nuance the heroic Heideggerian conception of death. Finally, Loren Eiseley hints at a possibility that only literature can afford. Instead of attempting to seize the world through culture or envying animals’ authenticity, human beings can acquire tangential perspectives upon their world and that of animals.